The Meaning of Profit for Canang Traders: A Phenomenological Study - Ni Made Ari Surya Mahayani; Ayudia Sokarina (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to uncover the meaning of profit from the perspective of Canang traders. This research uses qualitative research methods with phenomenology as a research approach. Data collection techniques involve observation, in-depth interviews, and documentation. The informant in this study is a Canang trader conducting business on Ismail Marzuki Street, Cakranegara District, Mataram City, West Nusa Tenggara. The result of the survey indicates that profit, based on the awareness of Canang traders, is interpreted as holistic profits. This means that profit encompasses not only material elements such as savings or reserves to increase business capital, meet the family’s economic needs, pay installments, and support social activities in the community. However, profits also contain humanist elements in the form of profits in the form of spiritual activities, namely the obedience in creating canang and offerings to express gratitude and devotion to God for all the blessings and sustenance provided; profit in the form of “karmaphala”, where everything obtained in business is believed to stem from the goodness or badness of one’s actions; and profits in the form of happiness derived from positive customer responses, including trust, satisfaction, and pleasure.